Peran Organization for Security and Cooperation in Europe (OSCE) pada Konflik Transnistria - Arie Kusuma Paksi; Muhammad Labib Ramadhani; Andini Hayu Agus Putri (Global Political Studies Journal, 2023)
This paper attempts to explain what efforts have been made by the Organization for Security and Cooperation in Europe (OSCE) to deal with the conflicts that occurred in Transnistria. OSCE is an intergovernmental cooperation organization in the field of defense and security. Transnistria is a region in Moldova. The history of this conflict occurred at a time of weakening influence until the collapse of the power of the Soviet Union. Which after Moldova's independence there was a group that declared independence from Moldova and made the name of a new country with the name Pridnestrovian Moldavian Soviet Socialist Republic or Transnistria. One of the triggers for this conflict is linguistic and cultural differences, where most Moldovan people are close to Romania while Transnistria is close to Slavic. This conflict caused many casualties, as well as ethnic and national sentiments from various groups. For this reason, OSCE, as the organization's defense and security organization, helps this conflict by carrying out several functions such as the Information function, regulatory function, and operational function. Keywords — OSCE, Conflict, Moldova, Transnistria